(untitled) (Actualité en allergologie et en immunologie au Canada, 2025)
Hymenoptera venom allergy (HVA), caused by stings from bees, wasps, hornets, and yellow jackets, is one of the most common identifiable causes of anaphylaxis in adults. While local reactions are common, systemic responses can be fatal. Venom immunotherapy (VIT) offers long-term protection and is often curative. Introduced in the 1920s, VIT remains the only disease-modifying treatment for HVA.